2015
DOI: 10.1039/c5ra16215g
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemistry of alkyl iodides: theoretical studies on the mechanisms and kinetics of CH3I/C2H5I + NO3reactions

Abstract: Mechanisms and kinetics of the reactions of the NO3 radical with CH3I and C2H5I have been investigated from a sound theoretical basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…As reported in previous studies the photolysis of the compound will take place if the vertical excitation energy is smaller than 4.13 eV or the wavelength is greater than 300 nm. , As shown in Figure and Table S7, it is observed that the absorption wavelength of sulfoxaflor and intermediate complexes is less than 300 nm, indicating photolysis is unlikely in the actinic flux. That is, sulfoxaflor and its derivatives will not photolyze, which is due to the presence of different functional groups in the studied compounds.…”
Section: Resultssupporting
confidence: 60%
“…As reported in previous studies the photolysis of the compound will take place if the vertical excitation energy is smaller than 4.13 eV or the wavelength is greater than 300 nm. , As shown in Figure and Table S7, it is observed that the absorption wavelength of sulfoxaflor and intermediate complexes is less than 300 nm, indicating photolysis is unlikely in the actinic flux. That is, sulfoxaflor and its derivatives will not photolyze, which is due to the presence of different functional groups in the studied compounds.…”
Section: Resultssupporting
confidence: 60%
“…For other intermediate complexes the absorption is very weak. As reported in previous studies, the compounds will undergo photolysis in sunlight only if the vertical excitation energy is smaller than 4.13 eV (∼300 nm). As shown in Figure , the dominant absorption for diuron is 220 nm and is in agreement with the experimental value of 214 nm .…”
Section: Photolysis Of Diuronsupporting
confidence: 57%
“…However, there are insufficient data to refine these estimates. Possible mechanisms for these reactions are discussed by Bai et al [37].…”
Section: Reactions Of No 3 With Iodidesmentioning
confidence: 99%
“…The data are much more consistent with assuming that the reactions of NO 3 with iodides is initiated by adding or associating with the I group, then reacting further. Theoretical studies of reactions of iodides with NO 3 radicals are discussed by Bai et al [37]. Therefore, for estimation purposes we treat reactions of NO 3 with iodides as additions, with the base rate constant that fits the data included in Table S16 in the SI.…”
Section: Reactions Of No 3 With Iodidesmentioning
confidence: 99%